Food safety, modernization, and food prices: Evidence from milk in Ethiopia - Minten, Bart; Habte, Yetimwork; Baye, Kaleab; Tamru, Seneshaw (International Food Policy Research Institute, 2020)
Modern marketing arrangements are increasingly being implemented to assure improved food quality and safety. However, it is not well known how these modern marketing arrangements perform in early stages of roll-out. We study this issue in the case of rural-urban milk value chains in Ethiopia, where modern processing companies – selling branded pasteurized milk – and modern retail have expanded rapidly in recent years. We find overall that the adoption levels of hygienic practices and practices leading to safer milk by dairy producers in Ethiopia are low and that there are no significant differences between traditional and modern milk value chains. While suppliers to modern processing companies are associated with more formal milk testing, they do not obtain price premiums for the adoption of improved practices nor do they obtain higher prices overall. Rewards to suppliers by modern processing companies are mostly done through non-price mechanisms. At the urban retail level, we surprisingly find that there are no price differences between branded pasteurized and raw milk and that modern retailers sell pasteurized milk at lower prices, ceteris paribus. Modern value chains to better reward hygiene and food safety in these settings are therefore called for.